Comprehensive bioinformatics analysis to identify a novel cuproptosis-related prognostic signature and its ceRNA regulatory axis and candidate traditional Chinese medicine active ingredients in lung adenocarcinoma - Wang, Shaohui; Xing, Nan; Meng, Xianli; Xiang, Li; Zhang, Yi (Frontiers in Pharmacology, 2022)
Lung adenocarcinoma (LUAD) is the most ordinary histological subtype of lung cancer, and regulatory cell death is an attractive target for cancer therapy. Recent reports suggested that cuproptosis is a novel copper-dependent modulated form of cell death dependent on mitochondrial respiration. However, the role of cuproptosis-related genes (CRGs) in the LUAD process is unclear. In the current study, we found that DLD, LIAS, PDHB, DLAT and LIPA1 in 10 differentially expressed CRGs were central genes. GO and KEGG enrichment results showed that these 10 CRGs were mainly enriched in acetyl-CoA biosynthetic process, mitochondrial matrix, citrate cycle (TCA cycle) and pyruvate metabolism. Furthermore, we constructed a prognostic gene signature model based on the six prognostic CRGs, which demonstrated good predictive potential. Excitedly, we found that these six prognostic CRGs were significantly associated with most immune cell types, with DLD being the most significant (19 types). Significant correlations were noted between some prognostic CRGs and tumor mutation burden and microsatellite instability. Clinical correlation analysis showed that DLD was related to the pathological stage, T stage, and M stage of patients with LUAD. Lastly, we constructed the lncRNA UCA1/ miR-1-3p /DLD axis that may play a key role in the progression of LUAD and screened nine active components of traditional Chinese medicine (TCM) that may regulate DLD. Further, in vitro cell experiments and molecular docking were used to verify this. In conclusion, we analyzed the potential value of CRGs in the progression of LUAD, constructed the potential regulatory axis of ceRNA, and obtained the targeted regulatory TCM active ingredients through comprehensive bioinformatics combined with experimental validation strategies. This work not only provides new insights into the treatment of LUAD but also includes a basis for the development of new immunotherapy drugs that target cuproptosis.